Pengajaran Filsafat dan Filsafat Praktis - Ohoitimur, Johanis (Jurnal Orientasi Baru, 2008)
Philosophy is not a construction of abstract concepts isolated from social reality and human experience. Yet, philosophy includes a study of language as well as logic and rhetoric. The nature of philosophy is determined by its genesis. Since the period of Greek philosophy, Socrates developed a philosophy as the fruit of a dialog with day-to-day human experience for attaining a higher degree of wisdom. All along its history, there were great philosophers who studied and developed a philosophical thought that address human problems or shed light to their questions. Indeed, a serious philosophical reflection is determined by its relevance and significance to the human struggle and experience.